The Potential Usage of Chickpea and Flaxseed Flours in Enhancing the Nutritional Value and Functional Properties of Gluten Free Flour - Al Ajeeli, Jamila; Ilowefah, Muna (Wadi Alshatti University Journal of Pure and Applied Sciences, 2026)
This study aimed to enhance the nutritional value and functional properties of laboratory prepared gluten free flour made from rice flour fortified with flour of chickpea and flaxseed and comparing that properties with that of commercial gluten free flour. The chemical parameters measured included moisture, ash, protein, fat and total fiber. Whereas, the measured functional properties involved water and oil binding capacity, swelling capacity, foaming ability and stability. The results showed significant differences between the two samples in most of the studied chemical indicators. The commercial flour had higher moisture content (11.34%) compared to the laboratory prepared flour (9.65%). However, the laboratory flour showed a higher protein content (11.84%) compared to the commercial flour (3.61%). Ash content was also higher in the laboratory flour (1.95%) in comparison to the commercial one (0.91%). A significant higher fat content was observed in the laboratory flour (3.90%) compared to the commercial flour (2.93%). No significant difference was found in crude fiber content between the two samples. Additionally, the findings recorded significantly greater calcium and phosphorus content in the laboratory flour. The results indicated that the commercial flour demonstrated higher water and oil binding capacities (211% and 131%, respectively) compared to the laboratory flour (66% and 80%, respectively). It also exhibited better swelling capacity (297 g/g) in comparison to the laboratory made flour (50.84 g/g). The commercial flour showed a noticeable foaming ability and stability, while the laboratory flour showed no foaming ability.